Antimicrobial drug resistance of Campylobacter spp and Salmonella enterica: national data in food producing animals and food of animal origin - Clemente, L. (2017)
Campylobacter spp and Salmonella enterica are the two most common causes of bacterial foodborne illnesses in humans in developed countries, being food producing animals one the main reservoirs. Antimicrobial susceptibility testing was determined through Minimum Inhibitory Concentration, in 448 isolates of Campylobacter spp recovered from broiler ceca at slaughter (n=351) and broiler carcasses (n=97); and 1600 isolates of S. enterica feed (n=43) and food products of animal origin (n=527). Screening and identification of beta-lactamase and plasmid-mediated quinolone resistance (PMQR) genes were performed by PCR and sequencing. The highest level of resistance in Campylobacter spp isolates recovered from broilers and carcasses was recorded to ciprofloxacin, followed by tetracycline, erythromycin and streptomycin. Four isolates of Campylobacter coli were resistant to gentamicin.